KONSEP ILAHIYAH : PEMIKIRAN KALAM SYAIKH NAWAWI AL-BANTANI - Faizi, Mohammad Ilham (El-Waroqoh : Jurnal Ushuluddin dan Filsafat, 2024)
Shaykh Nawawi al-Bantani was a scholar who followed the Asy'ariah view. He followed the theological concepts of Imam Abu Hasan al-Asari and Imam Abu Manshur al-Maturidi. The style of Shaykh Nawawi's kalam thought in the matter of divinity, on related themes, is characterized by classical kalam with Asy'ariyyah views in the matter of wahdaniyyah, God's power and will. While in the issue of God's nature, Nawawi combines Asy'ariyyah (kalam in the sense of qadim nature) with Maturidiyyah's theory of kalam nafsi. The method used in this research is a qualitative method with the type of library research (literature study). The result of this study is that according to Syaikh Nawawi Al-Bantani's thoughts about God's kalam is an azali and qadim nature. The word of God is purified (munazzah) from things that are hadith or new, he considers that the word of God in the sense of the nature of the qadim, is that which has no sound and letters like the current Al-Qur'an, and the Al-Qur'an and the qadim are two different things. God's speech in the sense of attributes is not new (hadith) but qadim, nor is it a creature (ghair makhluq) because it was not created.